2014
DOI: 10.1371/journal.pone.0111724
|View full text |Cite|
|
Sign up to set email alerts
|

Hypertriglyceridemic Waist and Metabolic Abnormalities in Brazilian Schoolchildren

Abstract: ObjectiveTo identify the prevalence of hypertriglyceridemic waist (HTW) phenotype and its association with metabolic abnormalities in schoolchildren.MethodsA cross-sectional study, with a sample of 241 students aged 10 to 14 years from public schools (4 schools) and private (2 schools) from Paranavai town, in Parana State, Brazil. Anthropometric variables (weight, height, waist circumference) and levels of triglycerides, total cholesterol, HDL-C, non-HDL and LDL-C were analyzed. In statistical tests of Pearson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Nationwide, Guilherme et al 21 obtained results similar to those found in this study in research with students aged 10 to 14 years from public and private schools in Paraná, of whom 20.7% presented simultaneously increased WC and serum TG. On the other hand, lower percentages have also been documented in the scientific literature.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Nationwide, Guilherme et al 21 obtained results similar to those found in this study in research with students aged 10 to 14 years from public and private schools in Paraná, of whom 20.7% presented simultaneously increased WC and serum TG. On the other hand, lower percentages have also been documented in the scientific literature.…”
Section: Discussionsupporting
confidence: 87%
“…16 Besides, as hypertriglyceridemia results from excessive carbohydrate consumption, and VLDL is a triglyceride-rich lipoprotein responsible for its transport to peripheral tissues, the association between abnormal VLDL and HTGW may be justified by the predominant glycemic inadequacy in the sample, since this lipoprotein is carbohydrate-dependent. Similarly, Conceição-Machado et al 21 also evidenced a correlation between this phenotype and the atherogenic lipid profile in a healthy population of the same age group, recommending the use of this tool as a practical way of screening children and adolescents with cardiometabolic abnormalities.…”
Section: Discussionmentioning
confidence: 80%
“…As already mentioned, the HTW picture includes the combination of abdominal obesity and elevated TG (dyslipidemia) and, in the present study, 27.9% of students presented this diagnosis. In 2014, in the same population and city, with the same classification criteria, the prevalence of HTW was 20.7% 6 , that is, in five years the incidence was 7.2%. Different prevalences have been reported in the literature, similar values have also been observed considering HTW assessments in different places around the world 26,27 , and in Brazil 2-28 , however, in all of them, the criteria and cutoff points were different.…”
Section: Discussionmentioning
confidence: 93%
“…The sample calculation resulted from the total number of the population (n=3.483); a prevalence of 20.7% of HTW in schoolchildren in the same city in 2014 6 confidence level equal to 95%; and sampling error of 4%. Based on these parameters, data from 354 students were required.…”
Section: Methodsmentioning
confidence: 99%
“… 22 Investigations involving Brazilian adolescents found the occurrence of HTW phenotype from 2.6% to 20,7%. 5 , 6 These differences among prevalence of HTW phenotype can reflect the lack of world standardization for measuring the waist circumference, and the serum concentrations of triglycerides for the age, moreover the variations of the cutoff used to classify the HTW phenotype, which is an obstacle to the comparison of the investigations. Besides, the differences of lifestyle, genetic background and ethnicity interfere with the accumulation of abdominal fat and can explain the divergent results of the HTW phenotype prevalence.…”
Section: Discussionmentioning
confidence: 99%